Intensity of exposure to pulmonary tuberculosis determines risk of tuberculosis infection and disease. Issue 1 (18th January 2018) - Acuña-Villaorduña, Carlos; Jones-López, Edward C.; Fregona, Geisa; Marques-Rodrigues, Patricia; Gaeddert, Mary; Geadas, Carolina; Hadad, David Jamil; White, Laura F.; Pereira Dutra Molina, Lucilia; Vinhas, Solange; Ribeiro-Rodrigues, Rodrigo; Salgame, Padmini; et al.
Household contacts of pulmonary tuberculosis (TB) patients are at increased risk of TB infection and disease. However, their risk in relation to the intensity of exposure remains unknown. We studied smear-positive TB cases and their household contacts in Vitória, Brazil. We collected clinical, demographic and radiographic information from TB cases, and obtained tuberculin skin test (TST) and QuantiFERON-TB Gold (QFT) results from household contacts. We measured intensity of exposure using a proximity score and sleep location in relation to the TB index case and defined infection by TST ≥10 mm or QFT ≥0.35 UI·mL −1 . We ascertained secondary TB cases by reviewing local and nationwide case registries. We included 160 TB index cases and 894 household contacts. 464 (65%) had TB infection and 23 (2.6%) developed TB disease. Risk of TB infection and disease increased with more intense exposures. In an adjusted analysis, the proximity score was associated with TB disease (OR 1.61, 95% CI 1.25–2.08; p<0.000); however, its diagnostic performance was only moderate. Intensity of exposure increased risk of TB infection and disease among household contacts; however, its diagnostic performance was still suboptimal. A biomarker to target preventive therapy is urgently needed in this at-risk population. More intense exposures are associated with higher risk of TB infection and disease among close contacts of TB cases http://ow.ly/PnQW30gapxK